Diffusion Jet Flame Models Using Open Source Code CFD Software - Suvanjumrat, Chakrit; Aroonjarattham, Panya (Agriculture and Natural Resources, 2015)
Open-source code software (OpenFOAM) based on computational fluid dynamics (CFD) was implemented and applied to simulate the diffusion of a jet flame. The large eddy simulation (LES) of the turbulence combustion model was written using the C++ language. The mixture fraction approach, an infinitely-fast chemistry assumption and radiative heat transfer were combined with this LES model. The finite volume method was performed to solve and simulate diffusion jet flame models under varying methane flow rates and environmental pressures. The results of the jet flame simulation comprising the percentage of maximum burning temperature, the heat release rate and oxygen from the oxygen fraction were defined to be the flame shape for validation with experiments. It was found that the flame length measured using the heat release rate from the results of simulations had the best agreement with the experiments. An average error of less than 5.84% was obtained by a comparison between the developed CFD model and the experiment when the CFD flame length was depicted by the heat release rate.